Effect of Content Marketing, Customer Engagement, and Brand Trust on Brand Loyalty (Survey on users of the “Bareksa” Digital Investment Platform) - Rifaldi, M. Diky; Gaffar, Vanessa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of content marketing, customer engagement, and brand trust on brand loyalty among users of the digital investment platform "Bareksa"). The data collection technique used a questionnaire with purposive sampling method and used a research sample of 100 respondents. The analysis in this study uses the SPSS program. The results of this study found that content marketing has no effect on brand loyalty. Meanwhile, customer engagement and brand trust have a significant positive effect on brand loyalty.